Severe hepatobiliary morbidity is associated with Clonorchis sinensis infection: The evidence from a cross-sectional community study. - Men-Bao Qian; Hong-Mei Li; Zhi-Hua Jiang; Yi-Chao Yang; Ming-Fei Lu; Kang Wei; Si-Liang Wei; Yu Chen; Chang-Hai Zhou; Ying-Dan Chen; Xiao-Nong Zhou (Public Library of Science (PLoS), 2021)
Clonorchis sinensis infection is highly prevalent in Asia. Diverse hepatobiliary morbidity has been documented for C. sinensis infection. This study aimed to assess the association between C. sinensis infection and hepatobiliary morbidity, taking into consideration of the control, confounders and infection intensity. A cross-sectional community survey was implemented in Hengxian county, southeastern China. Helminth infections were detected by fecal examination. Physical examination and abdominal ultrasonography were then conducted. After excluding confounding effects from gender, age and alcohol drinking, quantitative association between C. sinensis infection and hepatobiliary morbidity was assessed, and the effect from infection intensity was also evaluated, through adjusted odds ratio (aOR) and 95% confidence intervals (95% CI). 696 villagers older than 10 years were enrolled. The prevalence and infection intensity of C. sinensis were higher in male, elder people and the individuals consuming alcohol. Light C. sinensis infection was associated with the increase of diarrhoea (aOR: 2.2, 95% CI: 1.1-4.5). C. sinensis infection was associated with the increase of fatty liver (aOR: 2.7, 95% CI: 1.4-5.2), and the effect was similar in different infection intensities. Moderate C. sinensis infection was associated with the increase of gallbladder stone (aOR: 3.0, 95% CI: 1.1-8.6), while moderate and heavy infections with the increase of intrahepatic bile duct dilatation (aOR: 2.2, 95% CI: 1.0-4.9 and aOR: 4.3, 95% CI: 1.9-9.9, respectively). C. sinensis infection had an effect on the development of periductal fibrosis (aOR: 3.2, 95% CI: 2.1-4.9), which showed increasing trend by infection intensity. The length and width of gallbladder in those with C. sinensis infection were enlarged, especially in those over 30 years old. C. sinensis infection is significantly associated with hepatobiliary morbidity. The occurrence of some morbidity was strongly related to the infection intensity. Awareness on harm of clonorchiasis should be raised both for policy-makers and villagers to adopt effective interventions.